Characteristics of Young Children Close to the Onset of Stuttering. (May 2015) - Cavenagh, Penny; Costelloe, Sarah; Davis, Steve; Howell, Peter
Five factors (gender, handedness, some aspects of general health, family history, and intelligence) that could assist speech–language pathologists in identification of children who stutter (CWS) in 42 CWS and 34 fluent control children (children who do not stutter [CWNS]) were investigated. The data reported here were obtained from assessments made within 1 year of the reported onset of stuttering. The results from the initial assessments showed significant differences between CWS and CWNS on the five factors considered. Although there were some differences on intelligence scores, it is emphasized that the scores of all CWS were within normal limits, and in fact, both groups scored higher than the population average. These factors are important for the initial assessment of stuttering and may be useful for establishing what intervention is appropriate.